Effects of Single Pill-Based Combination Therapy of Amlodipine and Atorvastatin on Within-Visit Blood Pressure Variability and Parameters of Renal and Vascular Function in Hypertensive Patients with Chronic Kidney Disease. (7th April 2014) - Azushima, Kengo; Uneda, Kazushi; Tamura, Kouichi; Wakui, Hiromichi; Ohsawa, Masato; Kobayashi, Ryu; Dejima, Toru; Kanaoka, Tomohiko; Maeda, Akinobu; Toya, Yoshiyuki; Umemura, Satoshi
Abstract : Both strict blood pressure (BP) control and improvements in BP profile such as BP variability are important for suppression of renal deterioration and cardiovascular complication in hypertension and chronic kidney disease (CKD). In the present study, we examined the beneficial effects of the single pill-based combination therapy of amlodipine and atorvastatin on achievement of the target BP and clinic BP profile, as well as markers of vascular and renal damages in twenty hypertensive CKD patients. The combination therapy with amlodipine and atorvastatin for 16 weeks significantly decreased clinic BP, and achievement of target BP control was attained in an average of 45% after the combination therapy in spite of the presence of no achievement at baseline. In addition, the combination therapy significantly decreased the within-visit BP variability. With respect to the effects on renal damage markers, combination therapy with amlodipine and atorvastatin for 16 weeks significantly decreased albuminuria (urine albumin-to-creatinine ratio, 1034 ± 1480 versus 733 ± 1218  mg/g-Cr, P < 0.05 ) without decline in estimated glomerular filtration rate. Concerning parameters of vascular function, the combination therapy significantly improved both brachial-ankle pulse wave velocity (baPWV) and central systolic BP (cSBP) (baPWV, 1903 ± 353 versus 1786 ± 382  cm/s, P < 0.05 ; cSBP, 148 ± 19 versus 129 ± 23  mmHg, P < 0.01 ). Collectively, these results suggest that the combination therapy with amlodipine and atorvastatin may exert additional beneficial effects on renal and vascular damages as well as BP profile in addition to BP lowering in hypertension with CKD.